E2F/p107 and E2F/p130 complexes are regulated by C/EBPalpha in 3T3-L1 adipocytes. - Timchenko, N A (1999)
We have previously found that loss of C/EBPalpha in hepatocytes of newborn livers leads to increased proliferation, to a reduction in p21 protein levels and to an induction of S phase-specific E2F/p107 complexes. In this paper, we investigated C/EBPalpha-dependent regulation of E2F complexes in a well-characterized cell line, 3T3-L1, and in stable transformants that conditionally express C/EBPalpha. C/EBPalpha and C/EBPbeta proteins are induced in 3T3-L1 preadipocytes during differentiation with different kinetics and potentially may regulate E2F/Rb family complexes. In pre-differentiated cells, three E2F complexes are observed: cdk2/E2F/p107, E2F/p130 and E2F4. cdk2/E2F/p107 complexes are induced in nuclear extracts of 3T3-L1 cells during mitotic expansion, but are not detectable in nuclear extracts at later stages of 3T3-L1 differentiation. The reduction in E2F/p107 complexes is associated with elevation of C/EBPalpha, but is independent of C/EBPbeta expression. Bacterially expressed, purified His-C/EBPalpha is able to disrupt E2F/p107 complexes that are observed at earlier stages of 3T3-L1 differentiation. C/EBPbeta, however, does not disrupt E2F/p107 complexes. A short C/EBPalpha peptide with homology to E2F is sufficient to bring about the disruption of E2F/p107 complexes from 3T3-L1 cells in vitro. Induction of C/EBPalpha in stable 3T3-L1 clones revealed that C/EBPalpha causes disruption of p107/E2F complexes in these cells. In contrast, E2F/p130 complexes are induced in cells expressing C/EBPalpha. Our data suggest that induction of p130/E2F complexes by C/EBPalpha occurs via up-regulation of p21, which, in turn, leads to association with and inhibition of, cdk2 kinase activity. The reduction in cdk2 kinase activity correlates with alterations of p130 phosphorylation and with induction of p130/E2F complexes in 3T3-L1 stable clones. Our data suggest two pathways of C/EBPalpha-dependent regulation of E2F/Rb family complexes: disruption of S phase-specific E2F/p107 complexes and induction of E2F/p130 complexes.